The clinical application of ctDNA to predict response to neoadjuvant chemoradiotherapy in patients with locally-advanced rectal cancer - Parmida Sadat Pezeshki; Reza Ghalehtaki (BMC, 2023)
Abstract Colorectal cancer is a major cause of cancer-related deaths worldwide. A third of colorectal cancers reside in the rectum. Many patients with rectal cancer present in the locally-advanced stage which needs multi-modality therapy usually starting with neoadjuvant chemo-radiotherapy followed by surgery and adjuvant systemic chemotherapy. Total neoadjuvant therapy, defined as the preoperative administration of both neoadjuvant chemoradiotherapy and systemic chemotherapy is also an evolving treatment that can be delivered if indications for preoperative chemotherapy exist. Identifying biomarkers to predict response to neoadjuvant therapy, can improve patient selection for a non-surgical, active surveillance approach. Circulating tumor DNA (ctDNA) can be detected in about 75% of patients with locally-advanced rectal cancer (LARC) at the baseline and in about 15-20% of patients in the post-neoadjuvant, or postoperative setting. ctDNA clearance rate after delivering neoadjuvant chemoradiotherapy, or integrating baseline ctDNA with other conventional markers of clinical response can be a promising marker to select and monitor patients on the "watch and wait" approach. In this article, we aimed to integrate the recent findings and provide a unique insight into the utilization of preoperative ctDNA to predict clinical response in patients with LARC. We also sought to highlight the potential areas for future research in this field. Further studies with a larger number of participants from diverse populations and settings are needed to increase external validity of such investigations and determine the role of ctDNA in guiding clinical decisions and management of patients with LARC.